BIMBINGAN DAN PELATIHAN DESAIN LABEL KEMASAN PADA UKM KERUPUK DI DESA AMPELDENTO KARANGPLOSO - Rena Feri Wijayanti; Lina Budiarti; Erlangga Andi Sukma; Joni Dwi Pribadi; Shinta Maharani Trivena (P3M Politeknik Negeri Malang, 2020)
Small businesses such as home industries have to face various obstacles to expand their product markets. One of the obstacles is the products offered are not well known to the public because there is no brand label attached to the product packaging. Seeing the importance of brand labels on a product, it is important to be able to participate in small businesses to provide additional knowledge of the function and use of brand labels in product marketing. This community service aims to provide direction about the benefits of labels to introduce products to a wider market.